O avanço técnico do campo e as contradições infraestruturais do urbano em Campo Verde/MT - Souza, Daniel Borges de (2010)
Analyzing urbanization in the cities of the Brazilian agribusiness leads to social objectives that are set aside for capital interests prevail. It is true that since its creation after 1970 to the present, changes have occurred and are occurring in a dynamic indisputable. The origin of Green Field your analysis since the time of the Capim Branco until today that it mixes with agribusiness potential that transforms and intensifies the urbanization and urban expansion. Campo Verde and its socio-spatial organization that resembles several other cities like Lucas do Rio Verde and Sorriso whereas the pioneers who participated in the construction of this new city sought to maintain the urban model of southern Brazil. Its infrastructure whose elements range from the lack of basic sanitation to the development of technologies aimed at the citizen interaction campoverdense the internet world and this same technology has been used to create the digital city, a project that sank before even leaving paper, like others who are part of both digital and physical infrastructure. The use of space seeks to consider the actual need of the development and growth of the city. The traffic of motor vehicles not only as part of this infrastructure is also the most expensive in the creation of new routes and maintaining existing ones, not only the pathways that analyzed show concern, but the project never became effective for improving the city. The difficulties are a portrait of social contradictions that emerge in the landscape of this city that calls itself modern, but actually reveals a fallacy. Among many challenges Campo Verde and many other Brazilian cities is facing and overcoming difficulties such as the housing shortage and unemployment remain so among the most prosperous in the State of Mato Grosso.